Reconciling Religious Sentiments through Acculturation of Tampung Tawar Tradition in Ethnic Dayak in Kotawaringin Lama District - Agustin, Fitri; Fatimah, Nurul (Universitas Islam Negeri Raden Intan Lampung, 2026)
The tampung tawar tradition is one of the traditions of the Dayak Sekayu Darat sub-tribe with Kaharingan beliefs in Kotawaringin Lama District, Central Kalimantan Province. The main purpose of the tampung tawar tradition is to help each other for the sake of survival and the future of children. This study aims to identify the acculturation process that occurs in the tampung tawar tradition. In addition, it seeks to determine how this tradition can serve as a place of mediation in the reconciliation of religious conflicts in the Kotawaringin Lama community, using Albert Bandura's social cognitive theory. This study uses a qualitative method with an ethnographic approach through interviews and field observations. The results show that the tampung tawar tradition has undergone acculturation in its implementation and in the process of the child adoption ceremony. The acculturation that occurs illustrates the practice of interfaith tolerance because the tampung tawar tradition is not only practiced by the Kaharingan faith, but can also be practiced by other religions. This shows that the tampung tawar tradition has the potential to be an effective forum for the reconciliation of religious conflicts in a multicultural society. Keywords: Acculturation, Reconciliation, Tampung Tawar Tradition.